Listening woman - Hillerman, Tony (Harper & Row, 1978)
Indian policeman Joe Leaphorn enters on the strangest case of his career when an old Indian soothsayer and a young Indian girl are found murdered, and ends up investigating the strange kidnapping of a group of Boy Scouts and evading a plot on his own life.